Savoirs paysans autour des huiles d’olive, (zaytun, Olea europaea var. europaea) et d’oléastre, (əl-bərri, Olea europaea var. sylvestris) Rif, nord du Maroc - Yildiz Aumeeruddy-Thomas; Dominique Caubet (Revue d'ethnoécologie)
In this article, we are centrally interested in the products of the olive tree and oleaster in Northern Morocco and in the technical conditions used to obtain table olives and several types of oils, and in what these products represent for the inhabitants. We aim to understand if the Rif offers any peculiarity. We suggest that these techniques, knowledge and expertise on oils have influenced pre-domesticatory and breeding processes in Northern Morocco. We will also discuss the exchanges within the Arabic-speaking groups of the Rif on this subject, and especially between Ain Mediouna who are Jbala Arabic speakers and their neighbors, groups speaking a Bedouin Arabic dialect, the Ḥyayna with whom they exchange regularly. The joint ethnobotanic and linguistic joint approach, through the analysis of certain terms such as məslāl used to describe a type of wild olive oil, zitəl bərri məslāl, shows a binary classification of varieties of oils, which could have led to the selection of varieties of the same name spreading mostly in the North of Morocco. A remarkable diversity of types of oils bear different local names: zīt t-tǝṛyāq, ɛǝlwāna, zīt šāmiyya, zīt d-əl-bərri məslāl, zīt əl-bərri rqīq, zīt d-əl-ma, zīt ɛarūsa, etc. They correspond to extraction processes ranging from the oldest millstones and mills dating from the Neolithic, to the most modern. This diversity suggests that farmers in Northern Morocco have old and significant types of knowledge and know-hows about olive trees and the oleaster, including the mastering of the oleaster grafting techniques. This knowledge, threatened by the industrialization of the oil production in Morocco, are however of heritage value –both culturally and economically- and invaluable for local food security, and the maintenance of the varietal diversification process, a highly topical subject for sustainable development.